Developmental delay in communication among toddlers and its relationship to caregiving behavior among violence-exposed, posttraumatically stressed mothers. (November 2018) - Torrisi, R.; Arnautovic, E.; Pointet Perizzolo, V.C.; Vital, M.; Manini, A.; Suardi, F.; Gex-Fabry, M.; Rusconi Serpa, S.; Schechter, D.S.
Graphical abstract: Highlights: No relationship found between IPV-PTSD and child language development at ages 12–42 months. Observed maternal behavior was associated with child language development. Observed maternal caregiving behavior was also associated with maternal IPV-PTSD s. Abstract: Objectives: This study aimed to understand if maternal interpersonal violence-related posttraumatic stress disorder (IPV-PTSD) is associated with delayed language development among very young children ("toddlers"). Methods: Data were collected from 61 mothers and toddlers (ages 12–42 months, mean age = 25.6 months SD = 8.70). Child expressive and receptive language development was assessed by the Ages and Stages Questionnaire (ASQ) communication subscale (ASQCS) that measures language acquisition. Observed maternal caregiving behavior was coded from videos of 10-min free-play interactions via the CARE-Index. Correlations, Mann-Whitney tests, and multiple linear regression were performed. Results: There was no significant association between maternal IPV-PTSD severity and the ASQCS. Maternal IPV-PTSD severity was associated with continuous maternal behavior variables (i.e. sensitive and controlling behavior on the CARE-Index) across the entire sample and regardless of child gender. Maternal sensitivity was positively and significantly associated with the ASQCS. Controlling behavior was negatively and significantly associated with the ASQCS. Conclusions: Results are consistent with the literature that while maternal IPV-PTSD severity is not associated with child language delays, the quality of maternal interactive behavior is associated both with child language development and with maternal IPV-PTSD severity. Further study is needed to understand if the level of child language development contributes to intergenerational risk or resilience for relational violence and/or victimization.